2019
DOI: 10.1002/ecy.2795
|View full text |Cite
|
Sign up to set email alerts
|

Rapid nitrogen fixation by canopy microbiome in tropical forest determined by both phosphorus and molybdenum

Abstract: Biological nitrogen fixation is critical for the nitrogen cycle of tropical forests, yet we know little about the factors that control the microbial nitrogen fixers that colonize the microbiome of leaves and branches that make up a forest canopy. Forest canopies are especially prone to nutrient limitation because they are (1) disconnected from soil nutrient pools and (2) often subject to leaching. Earlier studies have suggested a role of phosphorus and molybdenum in controlling biological N‐fixation rates, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…When we did see responses, they occurred 1 d after Mo and P applications to soil during the dry season and 1 month after applications of Mo, P, and lime combined in the wet season. Our results were unexpected, given that all previous studies that tested Mo or P limitation on BNF in the tropics have demonstrated more prominent responses to Mo (Barron et al 2009, Winbourne et al 2017, to P Hobbie 2000, Reed et al 2013), or to both (Wurzburger et al 2012, Stanton et al 2019. This was particularly surprising considering that Mo limitation is seemingly widespread in temperate and boreal ecosystems (Horstmann et al 1982, Silvester 1989, Jean et al 2013, Rousk et al 2016, Perakis et al 2017, P erez et al 2017, spanning from temperate regions of relatively high Mo richness and deposition (Marks et al 2015, Perakis et al 2017 to boreal systems with relatively low Mo FIG.…”
Section: Mo or P Limitation Did Not Strongly Limit Bnfcontrasting
confidence: 70%
See 1 more Smart Citation
“…When we did see responses, they occurred 1 d after Mo and P applications to soil during the dry season and 1 month after applications of Mo, P, and lime combined in the wet season. Our results were unexpected, given that all previous studies that tested Mo or P limitation on BNF in the tropics have demonstrated more prominent responses to Mo (Barron et al 2009, Winbourne et al 2017, to P Hobbie 2000, Reed et al 2013), or to both (Wurzburger et al 2012, Stanton et al 2019. This was particularly surprising considering that Mo limitation is seemingly widespread in temperate and boreal ecosystems (Horstmann et al 1982, Silvester 1989, Jean et al 2013, Rousk et al 2016, Perakis et al 2017, P erez et al 2017, spanning from temperate regions of relatively high Mo richness and deposition (Marks et al 2015, Perakis et al 2017 to boreal systems with relatively low Mo FIG.…”
Section: Mo or P Limitation Did Not Strongly Limit Bnfcontrasting
confidence: 70%
“…The southeastern Amazon is a region where Mo and P limitation may be pronounced because soils are developed from old, stable surfaces with little to no parent material contribution (Quesada et al 2011) and where atmospheric inputs are very low (Mahowald et al 2008, Wong et al 2020 a ). While a handful of studies have assessed the simultaneous effects of Mo and P on free‐living BNF rates in the tropics, such as in Hawaii, Panama, Costa Rica, and Belize (Vitousek and Hobbie 2000, Barron et al 2009, Wurzburger et al 2012, Reed et al 2013, Winbourne et al 2017, Stanton et al 2019), these regions have higher weathering and atmospheric inputs, particularly from sea‐salt aerosols (Wong et al 2020 a ). In addition, these studies have either been short‐term experiments testing the addition of Mo and or P, or longer‐term studies with Mo added as a nutrient “cocktail” where responses to Mo alone have not been examined (Vitousek and Hobbie 2000, Barron et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Epiphytes face several constraints regarding nutrient acquisition, and the microbial community seems to provide a good dose of crucial elements such as fixed nitrogen (Stanton et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Epiphytes face several constraints regarding nutrient acquisition, and the microbial community seems to provide a good dose of crucial elements such as fixed nitrogen (Stanton et al, ). The presence of endophytic bacteria within the coralloid roots of Z. pseudoparasitica , many of whom have the potential to fix nitrogen, suggests that the species has an additional supply of nutrients in the challenging conditions that these epiphytes exist in.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation